English teachers’ practices and beliefs towards instructional media in Indonesia - Saiful Akmal; Diah Bunga Nastiti; Qudwatin Nisak M. Isa; Safrul Muluk; Yunisrina Qismullah Yusuf; Titin Arifa Maulida (International Journal of Evaluation and Research in Education (IJERE), 2024)
Teachers’ practices and beliefs about instructional media are crucial in teaching English, as they can motivate students’ enthusiasm if teachers use them engagingly. Despite their importance, teachers’ practices and beliefs regarding instructional media in Islamic secondary schools in Indonesia have received less attention. The purpose of this qualitative study was to discover how teachers used instructional media and their beliefs towards employing it to teach English. We gathered information from two female English teachers at selected Islamic junior high schools in Aceh, Indonesia through observations and interviews. The results revealed that teachers utilized photos, whiteboards, overhead projectors, and flashcards to teach English. In their English foreign language classrooms, they used instructional media to facilitate students’ learning by explaining the materials, and giving exercises. Teachers believed that instructional media could help boost students’ interest, facilitate the learning process, and promote the achievement of teaching and learning objectives. They specified that curriculum and topic lessons are essential factors to consider when selecting instructional media for teaching English. They alleged that students’ feedback, participation in seminars or workshops, self-discovery, and new curricula could all have an impact on their beliefs. Future research should look into potentially more comprehensive accounts of teachers’ practices and beliefs about instructional media in varied secondary school contexts as well as how engaged students in more interactive classroom activities.